Growing Greener: Creating a New Values-based Environmental Engagement Toolkit for SME Intermediaries. (September 2019) - Hampton, Sam; Blundel, Richard; Fawcett, Tina; Shaw, Chris
Abstract: This paper explores a radically different way of facilitating energy and environmental initiatives in small and medium-sized enterprises (SMEs). In terms of energy policy, smaller firms in Europe are exempted from most of the major fiscal and regulatory mechanisms that are applied to larger organisations. Policies to reduce energy demand and associated carbon emissions in SMEs are largely based on providing incentives, such as face-to-face support and grants for energy efficiency in buildings. Energy advisors are therefore key intermediaries, providing advice and encouraging the uptake of low carbon technologies and practices by SMEs. Previous studies have found that advisors often find it difficult to engage effectively with SME owners and managers, and that traditional 'win-win' messaging can have limited impact, resulting in implementation problems such as under-investment in energy-saving technologies, reluctance to adopt new environmental practices, and a tendency to revert to previous ways of operating once the incentive is removed. Recent research also suggests that SME owners' and managers' personal values play an important mediating role in their response to environmental issues, acting in combination with more established factors such as educational background, access to resources and the views of customers and suppliers. The implication is that policy interventions in this area could be delivered in more cost-effective ways if accompanied by a more nuanced, values-based approach to engagement. This paper reports findings from 'Growing Greener' a UK multi-disciplinary project that aims to equip advisors and other types of intermediary with the skills, knowledge and understanding they need in order to incorporate a values-based approach into their existing interactions with SMEs. It opens with an overview of the policy context and a brief overview of the relevant research literature. The main section explains how the research team co-produced a values-based engagement toolkit in conjunction with a group of energy advisors and external specialists. The design process included a series of facilitated 'narrative workshops', where advisors shared their experiences and experimented with early versions of the engagement tools. This is followed by an outline of the completed engagement 'toolkit', which includes free-to-access online course, a communication guide and an interactive engagement tool. These three inter-related components are designed to help advisors to engage SMEs beyond a narrow, cost-benefit framework, and in turn help SME owners and managers to connect low carbon choices with the personal and business values that are important to them as individuals. Our findings indicate the potential for more effective, longer-lasting interventions beyond the low hanging fruit of building efficiency measures.